IMPLEMENTASI PELAYANAN PENERBITAN AKTA KELAHRAN MELALUI PROGRAM INOVASI BUAH HATIKU DI KABUPATEN MAGETAN - Enis Tristiana; Ansori, Royaniah Khanza (EVOKASI: Jurnal Kajian Administrasi dan Sosial Terapan, 2023)
This study aims to analyze the implementation of Buah Hatiku innovation in Magetan Regency. The type of research used is descriptive empirical with a qualitative approach. Qualitative approach. Research data sources include primary data and secondary data. The results of this study show the implementation of the Buah Hatiku innovation in Magetan Regency, which has collaborated with three hospitals as partners. With three hospitals as partners. The implementation of this activity is in accordance with the Standard Operational Procedure (SOP) and has fulfilled the implementation indicators, which include aspects of communication, resources, disposition, and bureaucratic structure. Although it has been running well, This program still has obstacles. Although these obstacles only sometimes appear in every activity implementation, one example of these obstacles is the in complete requirements file from the applicant. The applicant needs to be completed. Thus, it can be concluded that the implementation of the Buah Thus, it can be concluded that the implementation of the Buah Hatiku innovation has been running well and has met the implementation indicators, and has obstacles that do not always appear in every activity implementation so that these obstacles can still be overcome.